Fishing in the commons: The effect of non-governmental organizations’ actions on illegal, unreported, and unregulated fishing - Kent Wicker; Annette Watson; Andrew M. Shedlock (Marine Policy, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

No association between markers of systemic inflammation and endothelial dysfunction with Alzheimer’s disease progression: a longitudinal study - Arne van Setten; Jeroen F. Uleman; René J. F. Melis; Brian Lawlor; Niels P. Riksen; Jurgen A. H. R. Claassen; Rianne A. A. de Heus; Ricardo Segurado; Sean Kennelly; Marcel G. M. Olde Rikkert; Robert Howard; Florence Pasquier; et al. (GeroScience, 2024)
Introduction Systemic inflammation and endothelial dysfunction are potentially modifiable factors implicated in Alzheimer’s disease (AD), which offer potential therapeutic targets to slow disease progression. Methods We investigated the relationship between baseline circulating levels of inflammatory (TNF-α, IL-1ß) and endothelial cell markers (VCAM-1, ICAM-1, E-selectin) and 18-month cognitive decline (ADAS-cog12) in 266 mild-to-moderate AD patients from the NILVAD study. We employed individual growth models to examine associations, potential mediation, and interaction effects while adjusting for confounders. Results The average increase in ADAS-cog12 scores over all patients was 8.1 points in 18 months. No significant association was found between the markers and the rate of cognitive decline. Mediation analysis revealed no mediating role for endothelial cell markers, and interaction effects were not observed. Discussion Our results do not support the role of systemic inflammation or endothelial dysfunction in progression in persons with AD.

Effect of dietary nitrate supplementation on thermoregulatory and cardiovascular responses to submaximal cycling in the heat - Georgina L. Kent; Brian Dawson; Gregory R. Cox; Chris R. Abbiss; Kurt J. Smith; Kevin D. Croft; Zi Xiang Lim; Annette Eastwood; Louise M. Burke; Peter Peeling (European Journal of Applied Physiology, 2018)

Taxonomic distinctness in the diet of two sympatric marine turtle species - Thomas B. Stringell; Wesley V. Clerveaux; Brendan J. Godley; Flora E. A. Kent; Emma D. G. Lewis; Jessica E. Marsh; Quinton Phillips; Peter B. Richardson; Amdeep Sanghera; Annette C. Broderick (Marine Ecology, 2016)
Marine turtles are considered keystone consumers in tropical coastal ecosystems and their decline through overexploitation has been implicated in the deterioration of reefs and seagrass pastures in the Caribbean. In the present study, we analysed stomach contents of green ( Chelonia mydas ) and hawksbill turtles ( Eretmochelys imbricata ) harvested in the legal turtle fishery of the Turks and Caicos Islands (Caribbean) during 2008–2010. Small juveniles to adult‐sized turtles were sampled. Together with data from habitat surveys, we assessed diet composition and the taxonomic distinctness (and other species diversity measures) in the diets of these sympatric marine turtle species. The diet of green turtles (n = 92) consisted of a total of 47 taxa: including three species of seagrass (present in 99% of individuals), 29 species of algae and eight sponge species. Hawksbill turtles (n = 45) consumed 73 taxa and were largely spongivorous (16 species; sponges present in 100% of individuals) but also foraged on 50 species of algae (present in 73% of individuals) and three species of seagrass. Plastics were found in trace amounts in 4% of green turtle and 9% of hawksbill turtle stomach samples. We expected to find changes in diet that might reflect ontogenetic shifts from small (oceanic‐pelagic) turtles to larger (coastal‐benthic) turtles. Dietary composition (abundance and biomass), however, did not change significantly with turtle size, although average taxonomic distinctness was lower in larger green turtles. There was little overlap in prey between the two turtle species, suggesting niche separation. Taxonomic distinctness routines indicated that green turtles had the most selective diet, whereas hawksbill turtles were less selective than expected when compared with the relative frequency and biomass of diet items. We discuss these findings in relation to the likely important trophic roles that these sympatric turtle species play in reef and seagrass habitats.

International Nursing Student Exchange: Rural and Remote Clinical Experiences in Australia - Arlene Kent-Wilkinson; Linda Starr; Sandra Dumanski; Jennifer Fleck; Annette LeFebvre; Amanda Child (Journal of Agromedicine, 2010)